Peningkatan Organizational Citizenship Behavior Melalui Penguatan Kepribadian dan Pemberdayaan Gutu Tetap Yayasan - Lia Oktapia; Rais Hidayat; Hendarman Hendarman (SAP (Susunan Artikel Pendidikan), 2023)
Organizational Citizenship Behavior (OCB) is one of the important factors that influence organizational performance. OCB refers to teachers' voluntary and proactive behaviour that is not included in the main job duties, but has a positive impact on organizational performance. In the context of foundations, OCB is important because foundations have a big role in improving the quality of education in Indonesia. However, there are still many foundations that have not paid attention to strengthening the personality and empowering their permanent teachers. Therefore, it is necessary to conduct research to evaluate the effectiveness of personality strengthening and empowerment of foundation permanent teachers in increasing OCB. This study aims to evaluate the effectiveness of personality strengthening and empowerment of foundation permanent teachers in increasing Organizational Citizenship Behaviour (OCB) in the work environment. The research method used is quantitative, with a sample consisting of permanent teachers at a foundation. Data obtained through questionnaires and analysed using regression analysis. The results showed that personality strengthening and empowerment of foundation permanent teachers had a significant positive effect on OCB. This research has implications for foundations in improving employee OCB through personality strengthening and empowerment, as well as contributing to further research in developing knowledge about the relationship between personality strengthening and empowerment with OCB.